Short QT Syndrome Presenting As Syncope: How Short Is Too Short? - Portugal, G (2014)
We report the case of a 52-year-old man who presented to our emergency department (ED) after three episodes of syncope in the seven hours before admission. During his stay in the ED he had recurrent ventricular tachycardia (VT) requiring external electrical cardioversion. A 12-lead electrocardiogram (ECG) showed a short QT (SQT) interval (270 ms, QTc 327 ms), with frequent R-on-T extrasystoles triggering sustained polymorphic VT. After exclusion of other precipitating causes, the patient was diagnosed as having SQT syndrome (SQTS) according to the Gollob criteria. To our knowledge, this is the first known documentation of an SQT-caused arrhythmic episode on a 12-lead ECG, as well as the first reported case of SQTS in Portugal. The patient received an implantable cardioverter-defibrillator and was discharged. At a follow-up assessment 14 months later he was symptom-free, interrogation of the device showed no arrhythmic events, and the ECG showed a QT interval of 320 ms (QTc 347 ms).